TRADISI MAKAN BAJAMBA DALAM ALEK PERKAWINAN DI NAGARI MAGEK PROVINSI SUMATERA BARAT - Mita Gustina; Basri " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Makan bajamba is a vernacular tradition from Minangkabau, for example  it be held often in wedding alek (party). The  process of makan bajamba in wedding party often see the combination to other culture. But, the  process is still the same, it is just the combination is not out of context of makan bajamba. Like, recitation of pasambahan by juaro, how  to put down the dishes and the dishes that will be delivered to ninik mamak and invited guests. Purpose of this study was to find out the process of makan bajamba in Nagari Magek  and moral value we get after makan bajamba ends. This study used method of  qualitative descriptive with 9 people as subject. Result of this study was  process of makan bajamba is still ongoing in Nagari Magek with custom  procedures that is still match the ancestors rules. Implementation of the process is still match with custom rules that applied in Nagari Magek, like recitation of pasambahan at before and after makan bajamba, participation of juaro to arrange the dishes and how to put down the dishes in the middle of ninik mamak and other invited guests matched the rules, and seat positions in makan bajamba which is different between ninik mamak and other invited guests. On process of makan bajamba also found few of moral value or positive implication like appreciate and respect the older with let them to take the food first, habituate ourselves to  sharing, also to establish the rope of unity to make it stronger and tighten the relationship. Makan bajamba gives inner satisfaction after doing it because it be held with praying together afterwards.  Keyword: The Tradition,Makan Bajamba, Pasambahan, Juaro.